Study on Potential Utilization of New Renewable Energy to Support the Electricity System in Warudoyong Area - Imam Abdul Khamid (FIDELITY : Jurnal Teknik Elektro, 2022)
Energy is one of the most basic human necessities for supporting activities that continue to expand in number as the population and economy rise. On the other hand, the majority of today's energy originates from fossil-based electricity, which has non-renewable qualities, meaning that its reserves will deplete if consumed indefinitely. In particular, Indonesia and the Warudoyong region of West Java Province have a diverse range of new and renewable energy (EBT) possibilities dispersed across the majority of their territory, ranging from solar energy, wind energy, bioenergy, marine energy, and geothermal. The goal of this study is to map the potential of EBT in the Warudoyong area in order to aid the government's goal of achieving the national energy mix and supporting energy diversification in the power system. The findings of the study show that there is a lot of renewable energy potential in the Warudoyong area, which can be converted into electrical energy